IMPLIKASI TEORI AKUNTANSI POSITIF DAN TEORI KEAGENAN DALAM PRAKTIK MANAJEMEN LABA - Suripto, Suripto; Supriyanto, Supriyanto (Jurnal Paradigma, 2021)
The purpose of this study is to test positive accounting theory by analyzing the effect of audit committees, independent commissioners on earnings management through debt hyphothesis testing, bonus motivation on earnings management, by adding the firm size variable as a control variable on earnings management in banking companies listed on the Indonesia Stock Exchange 2015-2020. The results of the study confirm that the independent commissioners partially have a significant influence on earnings management. The audit committee has a significant effect on earnings management and bonus motivation has no effect on earnings management and debt motivation has no effect on earnings management. While the firm size variable has no effect on earnings management. Simultaneously independent commissioners, audit committee, bonus motivation, and firm size have a significant effect on earnings management. This findings indicates that the motivation developed in positive accounting theory in earnings management.